Investigating lubricin and known cartilage-based biomarkers of osteoarthritis. (2nd April 2020) - Ravalli, Silvia; Szychlinska, Marta Anna; Lauretta, Giovanni; Di Rosa, Michelino; Musumeci, Giuseppe
ABSTRACT: Introduction : Osteoarthritis (OA) is a degenerative disease which primarily affects hyaline cartilage, leading to pain, stiffness and loss of mobility of the entire articulation. Diagnosis is commonly based on symptoms and radiographs, but there is a growing interest in detecting novel biomarkers, in serum, urine and synovial fluid, which can be predictors of disease onset and progression. Areas covered : This review provides an overview of the main biomarkers currently used in OA clinical practice, with a focus on lubricin, a surface glycoprotein secreted in the synovial fluid that lubricates the cartilage and reduces the coefficient of friction within the joint. Key findings of the last years are presented throughout the article. Expert opinion : Analysis of biomarkers might suggest personalized protocols of treatment, guide the classification of OA phenotypes, contribute to precision medicine, avoid further unnecessary exams, facilitate drug discovery or refine treatment guidelines. For all these reasons, the investigation of novel cartilage-based biomarker of osteoarthritis needs to be promoted and improved.